The Impact of Digital Transformation on Social Relations in Learning: A Study of the Transition to Virtual Learning Spaces - Hasnawati, Hasnawati; Erdawati, Mega; Asrijal, Andi (Socious Journal, 2026)
Digital transformation has shifted the learning process from physical to virtual spaces, influencing patterns of interaction and social relations between students and educators. This study uses a qualitative approach with a phenomenological method to understand the subjective experiences of students and educators regarding changes in social relations during virtual learning. The research subjects consisted of 15 students and 5 educators selected through purposive sampling. Data were collected through in-depth interviews, virtual observations, and digital documentation, then analyzed using Colaizzi's phenomenological stages. The results show that social relations in virtual learning spaces tend to be more functional, influenced by the intensity of digital interaction, technological access and literacy, communication ethics, social identity, and emotional aspects of students. The gap in digital access and capabilities creates new social stratifications that affect student participation and engagement. Changes in communication ethics and psychological pressures, including anxiety about appearing in front of a camera, also affect social cohesion. Group collaboration and support between students are important factors in building social closeness. Teachers have a strategic role in creating digital learning spaces that support healthy social interactions. The findings of this study provide theoretical and practical contributions to the development of learning strategies that maintain the quality of social relations in the digital era.